Coalescence of sessile microdroplets subject to a wettability gradient on a solid surface - Ahmadlouydarab, Majid; Lan, Chuanjin; Das, Arup Kumar; Ma, Yanbao (Physical review. E, 2016)
While there are intensive studies on the coalescence of sessile macroscale droplets, there is little study on the coalescence of sessile microdroplets. In this paper, the coalescence process of two sessile microdroplets is studied by using a many-body dissipative particle dynamics numerical method. A comprehensive parametric study is conducted to investigate the effects on the coalescence process from the wettability gradient, hydrophilicity of the solid surface, and symmetric or asymmetric configurations. A water bridge is formed after two microdroplets contact. The temporal evolution of the coalescence process is characterized by the water bridge's radii parallel to the solid surface (W_{m}) and perpendicular to the solid surface (H_{m}). It is found that the changes of both H_{m} and W_{m} with time follow a power law; i.e., H_{m}=β_{1}τ^{β} and W_{m}=α_{1}τ^{α}. The growth of H_{m} and W_{m} depends on the hydrophilicity of the substrate. W_{m} grows faster than H_{m} on a hydrophilic surface, and H_{m} grows faster than W_{m} on a hydrophobic surface. This is due to the strong competition between capillary forces induced by the water-bridge curvature and the solid substrate hydrophobicity. Also, flow structure analysis shows that regardless of the coalescence type once the liquid bridge is formed the liquid flow direction inside the capillary bridge is to expand the bridge radius. Finally, we do not observe oscillation of the merged droplet during the coalescence process, possibly due to the significant effects of the viscous forces.